Complex consanguinity associated with short rib-polydactyly syndrome III and congenital infection-like syndrome: a diagnostic problem in dysmorphic syndromes. Issue 6 (1st June 1999) - Al-Gazali, L I; Sztriha, L; Dawodu, A; Varady, E; Bakir, M; Khdir, A; Johansen, J
Abstract : Short rib-polydactyly syndromes (SRPS) are a heterogeneous group of recessively inherited lethal skeletal dysplasias. Four types have been recognised. However, overlap in the clinical and radiological features of the four types has led to difficulties in distinguishing between them. The congenital infection-like syndrome is an autosomal recessive syndrome characterised by mental retardation, microcephaly, seizures, and intracranial calcifications. We report a complex consanguineous family of Baluchi origin in whom short rib-polydactyly type III and congenital infection-like syndrome are segregating. Four children inherited SRPS III, one inherited congenital infection-like syndrome, and one inherited both. Although the radiological features in all the children with SRPS in this report were typical of type III, there was overlap in the clinical features with the other types of SRP syndromes. Furthermore, the child who inherited both SRPS III and congenital infection-like syndrome had CNS malformations in addition to periventricular calcification. CNS malformations have been described in SRPS types II and IV but not type III. This report further highlights the overlap between the different types of SRP syndrome. Moreover, it draws attention to the importance of considering the possibility of two recessive syndromes in the same child in complex consanguineous families when features overlap two syndromes.